Major ozonated autohemotherapy promoted functional recovery following spinal cord injury in adult rats via the inhibition of oxidative stress and inflammation - Xia Liwei; Sun Yongming; Zhou Yue; Yang Qian; Huang Jianhan; Liu Dong (Open Life Sciences)
This study sought to explore the value of major ozonated autohemotherapy (MOA) as a treatment for spinal cord injury (SCI) in a rat model system. In total, 54 female Sprague-Dawley rats were randomized into sham-operated, SCI model, and MOA treatment groups. We found that relative to the SCI model group, rats that underwent MOA treatment exhibited improved locomotor scores on days 14, 21, and 28 after injury (p < 0.05) together with reduced residual urine on days 5, 7, 14, and 21 after injury (p < 0.05). MOA treatment also lowered proinflammatory TNF-α, IL-1α, and C1q levels on day 3 post-injury (p < 0.05), decreased malondialdehyde levels, and enhanced superoxide dismutase activity (p < 0.001). Activated astrocytes in MOA-treated rats exhibited larger soma and higher levels of extracellular matrix secretion, whereas reactive microglia in the MOA group presented with a ramified morphology in contrast to the amoeboid morphology exhibited by these cells in SCI model rats. MOA offers potential value as a means of protecting spinal cord integrity, potentially through anti-inflammatory, antioxidant, and regulatory effects that shape the polarization of astrocytes and microglia.